We know that the slope-intercept form of an equation is represented by:
y = mx + b
Where m is the slope, b is the y-intercept, and x and y pertain to points on the line in the graph.
So the slope of the line is know to be 3, and we are able to plug that into the equation:
y = 3x + b
We also know that the point (-2, 6) is on the line. With this information, we can then plug in the point into the equation to find b:
6 = 3(-2) + b
Then we can solve for b:
6 = -6 + b
b = 12
Knowing that b is 12, we can then rewrite the equation in a more general slope-intercept form that is applicable to any point on that line:
y = 3x + 12
Thus, your answer would be C.